Analisis Peran Remunerasi dan Budaya Organisasi Terhadap Kompetensi Pegawai Guna Meningkatkan Kinerja Pegawai di Lembaga Penerbangan dan Antariksa Nasional - Leny Maryesa; Anggraini Sukmawati; Hari Wijayanto (Institut Pertanian Bogor, 2016)
Ideally the performance of a Government employees (PNS) aretheir service to the community in living and meeting their daily needs. The final goal of the PNS none other than to improve the welfare of society. Government Remuneration is an integral part of bureaucratic reform policy. Base on the bureaucracy awareness and also the government commitment to create a clean and good governmance. The purpose of bureaucratic reformation is to build a public trust (public trust building) and eliminate the negative image of government bureaucracy. The bureaucratic reformation vision is the establishment of the State apparatus professional and good governance. The mission is to change the pattern of bureaucratic reform mindset, cultural set, and the system of governance. Implementation of remuneration applied at LAPAN on July 2013 granted in accordance with the competences of the employees, work performance of the employees, and work discipline. The objective of this analysis is to analyze the relationship with remuneration and organizational culture, and the influence of remuneration to the employee competencies, organizational culture on employee competencies, employee competence to employee performance, remuneration to employee performance and the influence of organizational culture on employee performance. Analysis of the data used in this research is Structural Equation Modeling (SEM). The results of Study in simultaneously and partially are known to constructs remuneration, organizational culture, and employee competence positive effect on the performance of employees at every level positions and there is a correlation relationship between Construct Remunerasi and Cultural Organization to all employees and the level of structural positions and Special and strong correlation relationships at the level of the General Functional